Avaliação da permeabilidade in vitro e da solubilidade em equilíbrio de kavaína isolada e em extrato seco de kava-kava. - Rafael Rocha da Silva Santos (2021)
Kava-kava (Piper methysticum G. Forst) is a perennial shrub, belonging to Piperaceae family, from the archipelagos of South Pacific Ocean and used as a medicinal plant since 1000 BC. It has an action in the central nervous system and is used in the treatment of insomnia, agitation, stress, epilepsy, psychosis and depression. The pharmacological effect is due to the presence of kavalactones, mainly kavain found in rhizomes. Previous studies of our research group demonstrated that the oral bioavailability of kavain was considerably higher when it was administered in dry extracts of kava-kava, compared to its administration in the isolated form. Thus, we aimed, with this study, to conduct a biopharmaceutical evaluation of this compound isolated and in dry extracts of kava-kava. The HPLC-DAD methods developed for kavain quantitation in the studies were linear, precise, exact, selective and with satisfactory robustness. Equilibrium solubility studies carried out by the orbital shake flasks method at buffer solutions pH 1.2; 4.5 and 6.8 demonstrated dose /solubility ration higher than 250 mL, being respectively 1311.2 mL; 2888.7 mL; 1445.4 mL for kavain and 1450.5 mL; 1103.7 mL e 1279.3 mL for the extract. Results of the intestinal permeability study showed that both kavain alone and in the presence of kava kava dry extract presented high permeability values, with Papp values varying from 25 ± 1.45 to 28 ± 2.75 cm.s-1 . It was observed no significant efflux mechanism. The plant marker can be considered a compound with low solubility, and its dissolution in a physiological fluid is the limiting factor for absorption.